Mode I interlaminar fracture of woven glass/epoxy multidirectional laminates - Pereira, A.B.; De Morais, A.B.; De Moura, M.F.S.F.; Magalhaes, A.G.
Mode I Double Cantilever Beam (DCB)tests were performed on woven glass/epoxy multidirectional laminates. Selected specimen stacking sequences with starter delaminations in q/Kq and 0/q interfaces were first evaluated with three-dimensional finite element (FE)models. During the DCB tests, most specimens suffered intraply damage and crack branching to a neighbouring interface. Nevertheless, it was generally possible to measure valid interlaminar critical strain energy release rates,GIc, of initiation from the film and from a mode I precrack. The former were significantly lower than the latter due to steep R-curve effects. GIc values of 0/q specimens were fairly q-independent, while q/Kq specimens exhibited higher GIc from the film. A subsequent FE analysis provided explanations for the interface effect on GIc.
Keywords: POLYMER-MATRIX COMPOSITES (PMCS); LAMINATES; DELAMINATION; FRACTURE TOUGHNESS; FINITE ELEMENT ANALYSIS (FEA)